A CLINICO- COMPARATIVE STUDY TO EVALUATE THE EFFECT OF GUGGULUADI DRAVYAS KARNDHOOPAN WITH AND WITHOUT RASNADI GUGGULU IN KARNSRAVA (International Journal of Ayurveda and Pharma Research, 2020)
Karnsrava is a type of Karnaroga, explained by Acharya Sushruta in the 20th chapter named as Karnaroga Vigyaniya of Uttara tantra. Karnsrava comprises of broad spectrum of diseases under it. And it is hard to find correct correlation of otomycosis with any of the Karnarogas. In the present study otomycosis is one of the reasons of otorrhoea/ Karnsrava which is taken for the study. Otomycosis is a fungal infection of the ear canal that often occurs due to Aspergillus niger, A.fumigatus or Candida albicans. Management of otomycosis can be challenging because of its high recurrence rate and of the limited therapeutic options. Keeping in view all these facts, a randomized clinical trial was done in PG department of Shalakya Tantra, Patanjali Ayurvedic college & hospital, Haridwar. 60 patients were selected and divided into two groups namely group A and group B each consisting of 30 patients. Group A patients were treated with Gugguluadi Dravyas Karndhoopan twice daily for 7 days and Rasnadi guggulu vati twice daily after meal with lukewarm water for 30 days. And Group B patients were treated with Gugguluadi Dravyas Karndhoopan twice daily for 7 days and placebo capsules twice daily after meal with water for 30 days. Dhoopan is most effective therapy for Karnsrava- otomycosis and Karndhoopan is a simple, cost effective procedure which can be done even at the OPD level. Dhoopan dravyas has anti- fungal, anti- microbial, analgesic and anti- inflammatory properties. It was observed in the present study that group A showed better results than group B. Gugguluadi dravyas karndhoopan and Rasnadi Guggulu vati are safe, cost effective and free from any side effects in the management of Karnsrava.